A randomized controlled trial of a multicomponent, targeted, low‐literacy educational intervention compared with a nontargeted intervention to boost colorectal cancer screening with fecal immunochemical testing in community clinics. Issue 8 (1st December 2016) - Davis, Stacy N.; Christy, Shannon M.; Chavarria, Enmanuel A.; Abdulla, Rania; Sutton, Steven K.; Schmidt, Alyssa R.; Vadaparampil, Susan T.; Quinn, Gwendolyn P.; Simmons, Vani N.; Ufondu, Chukwudi B.; Ravindra, Chitra; Schultz, Ida; et al.
Abstract : BACKGROUND: The objective of the current study was to improve colorectal cancer (CRC) screening uptake with the fecal immunochemical test (FIT). The current study investigated the differential impact of a multicomponent, targeted, low‐literacy educational intervention compared with a standard, nontargeted educational intervention. METHODS: Patients aged 50 to 75 years who were of average CRC risk and not up‐to‐date with CRC screening were recruited from either a federally qualified health center or a primary care community health clinic. Patients were randomized to the intervention condition (targeted photonovella booklet/DVD plus FIT kit) or comparison condition (standard Centers for Disease Control and Prevention brochure plus FIT kit). The main outcome was screening with FIT within 180 days of delivery of the intervention. RESULTS: Of the 416 participants, 54% were female; the participants were racially and ethnically diverse (66% white, 10% Hispanic, and 28% African American), predominantly of low income, and insured (the majority had county health insurance). Overall, the FIT completion rate was 81%, with 78.1% of participants in the intervention versus 83.5% of those in the comparison condition completing FIT ( P =  .17). In multivariate analysis, having health insurance was found to be the primary factor predicting a lack of FIT screening (adjusted odds ratio, 2.10; 95% confidence interval, 1.04‐4.26 [ P =  .04]). CONCLUSIONS: The multicomponent, targeted, low‐literacy materials were not found to be significantly different or more effective in increasing FIT uptake compared with the nontargeted materials. Provision of a FIT test plus education may provide a key impetus to improve the completion of CRC screening. The type of educational material (targeted vs nontargeted) may matter less. The findings of the current study provide a unique opportunity for clinics to adopt FIT and to choose the type of patient education materials based on clinic, provider, and patient preferences. Cancer 2017;123:1390–1400. © 2016 American Cancer Society . Abstract : Disparities in colorectal cancer screening among medically underserved communities are addressed in an intervention to increase the uptake of the fecal immunochemical test (FIT). Although there do not appear to be any significant differences in FIT uptake between the targeted and nontargeted intervention conditions, high FIT uptake rates suggest that the provision of a FIT kit removes a crucial barrier to care.